T‐cell receptor‐δ expression and γδ+ T‐cell infiltrates in primary cutaneous γδ T‐cell lymphoma and other cutaneous T‐cell lymphoproliferative disorders. Issue 4 (27th July 2018) - Pulitzer, Melissa; Geller, Shamir; Kumar, Erica; Frosina, Denise; Moskowitz, Alison; Horwitz, Steven; Myskowski, Patricia; Kheterpal, Meenal; Chan, Alexander; Dogan, Ahmet; Jungbluth, Achim
Abstract : Aims: The diagnosis of cutaneous γδ T‐cell lymphoma (GDTCL) requires the identification of γδ chains of the T‐cell receptor (TCR). Our aim in this study was, by using a new monoclonal antibody (mAb) against TCRδ, to evaluate TCRδ expression in formalin‐fixed paraffin‐embedded (FFPE) skin tissue from TCRγ+ cutaneous T‐cell lymphoma (CTCL), and to assess TCRδ expression within a spectrum of other cutaneous lymphoproliferative disorders (CLPDs). Methods and results: Twelve cases (10 patients) with TCRγ+ CTCL and 132 additional CLPD cases (127 patients) were examined, including mycosis fungoides (MF) ( n = 60), cutaneous GDTCL ( n = 15), subcutaneous panniculitis‐like T‐cell lymphoma (SPTCL) ( n = 11), and CD30 + lymphoproliferative disorder (LPD) ( n = 24). Clone H‐41 against TCRδ was used on a Leica Bond‐3 automated stainer to label FFPE slides. H‐41 immunostaining was graded as percentage infiltrate: high (50–100%), moderate (10–49%), and low (0–9%). In TCRγ+ tumours, 12 of 12 (100%) patients showed TCRδ expression comparable to TCRγ expression. No (0%) TCRγ+ cases were negative for TCRδ. In all CLPDs, TCRδ expression was as follows: GDTCL, 16 of 20 cases (14 of 15 patients) high, two moderate, and two low; MF, 0 of 60 cases high, nine moderate, and 51 low; CD30 + LPD, one of 24 cases high, two moderate, and 21 low; and SPTCL, 0 of 11 cases (0 of 9 patients) high, two moderate, and two low. Three MF‐like cases and one SPTCL‐like case showed high expression; the remainder showed low expression. Conclusions: mAb H‐41 against TCRδ matches TCRγ in immunostaining FFPE tissues from GDTCL, supporting H‐41 as a replacement for mAb γ3.20. TCRδ expression in our study suggests that the true occurrence of γδ+ non‐GDTCL CTCL/CLPD may be lower than suggested by the recent literature.